Thermo‐cryogenic controls of fracture kinematics in permafrost rockwalls. Issue 8 (22nd April 2017) - Draebing, D.; Krautblatter, M.; Hoffmann, T.
Abstract: Thermo‐cryogenic processes prepare and trigger rockfalls and rockslides in alpine environments. Temporal occurrence, controls, and applied stresses of Thermo‐cryogenic processes on rock masses are poorly understood. This paper reports annual crackmeter measurements with 3 h resolution across perennially ice‐filled fractures in an unstable rock permafrost crestline. Thermo‐cryogenic processes are controlled by snow cover onset and duration. Thermal changes in snow‐free periods control expansion and contraction coincident temperature gradients on a daily to seasonal scale. We can show how snow cover promotes sustained temperatures from −9 to −1°C and boosts ice segregation‐related fracture opening up to 1 cm in 8 months. During snowmelt, meltwater induces ice erosion and ice relaxation, which occur in the freeze‐thaw window close to the thawing point. We hypothesize that Thermo‐cryogenic processes and their cyclic repetition can lead to Thermo‐cryogenic fatigue preparing rock slope failure and can control type and location of rockfalls in a changing climate. Key Points: Thermo‐cryogenic processes preparing and triggering rockfalls are controlled by snow cover Thermal changes control temperature‐gradient‐dependent rockwall expansion in snow‐free periods Snow cover boosts ice segregation‐related fracture opening